Implementasi FWEG (Fun Wordwall Energi Game) Sebagai Media Pembelajaran Interaktif Dalam Meningkatkan Literasi Sains - Aisya Rahma Fadhilla; Fadia Rusydiyanti (LPPM Universitas Terbuka, 2025)
This study aims to describe the implementation of FWEG (Fun Wordwall Energy Game) as an interactive learning medium in improving the science literacy of elementary school students. FWEG is a word-based media designed to help students understand the concept of energy in a fun and meaningful way. This study uses a qualitative approach with a descriptive method. The subjects of the study were grade V students in one of the public elementary schools, with data collection through observation, interviews, and documentation. The results of the study show that the application of FWEG is able to increase students' active involvement in learning, facilitate the understanding of energy concepts, and encourage students to think critically and communicatively. In addition, students showed high enthusiasm in following the learning process using FWEG, which had a positive impact on improving their science literacy. Thus, FWEG can be an effective alternative learning media to support the development of students' science literacy at the elementary school level.